Dietary diversity among school age children in Merawi town, Amhara region, Ethiopia, 2018: a community based cross-sectional study - Tilahun Tewabe; Amare Belachew; Yihun Miskir; Getnet Mekuria (BMC, 2020)
Abstract Background Malnutrition with its constituents of protein energy malnutrition and micro-nutrient deficiencies continues to be a major health burden in low and middle-income countries. To end all forms of malnutrition, we need to address poverty, which is associated with the insecure supply of food and diversified nutrition. The objective of this study was to determine the level of dietary diversity and household food security among urban school-age children in Merawi town, Ethiopia. Methods A community based cross-sectional study was conducted in Merawi town among 422 households having school age children from April 1 to June 15, 2018. The association between dietary diversity and determinants was assessed using binary logistic regression analysis. Socio-demographic, maternal and child related variables; food security and diversity determinants were studied. Results The overall level of good dietary diversity was 91.7%, i.e.; 8.3% had a low, 59.1% had a good, 32.6% had better dietary diversity, respectively. Most households (95.2%) were secured with food access. The factors associated with good dietary diversity were the age of the child [AOR = 0.31 (0.14, 0.70)], and access to information [AOR = 3.18 (1.07,9.47)]. Conclusion The prevalence of good dietary diversity was relatively high. Among different socio-cultural and economic factors studied, age of the child and access to information were the factors associated with dietary diversity. Increasing maternal and child awareness towards good dietary diversity practices through the mass media (radio and Television) and working with mothers with early school-age children to improve dietary diversity are recommended.